CORRELATION BETWEEN THE RADIOGRAPHERS WORKING TIME WITH PROCEDURES COMPREHENSION OF INTRA ORAL PERIAPICAL RADIOGRAPHIC IMAGING TECHNIQUE (Analytical Observation at Ulin Hospital and Gusti HasanAmanof Dental Hospital in Banjarmasin) - Afifah Rahmiati; Bayu Indra Sukmana; Isnur Hatta (Dentino : Jurnal Kedokteran Gigi, 2018)
Background: Radiography is an examination to observe the internal body using wave radiation. Radiography can be performed with oral and extra oral projection. The appropriate results of radiographic images and quality are influenced by the radiographers comprehension. Objective: Analyze the correlation between radiographers working time with procedures comprehension of intra oral periapical radiographic imaging technique at Banjarmasin Hospital. Method: This study is analytical observation with Cross Sectional approach. In this study 17 respondents became the study subject. Respondents at RSUD Ulin and RSGM Gusti Hasan Aman in Banjarmasin were given a questionnaire. Results: From 17 respondents, 6 people (85.7%) have less comprehension with working time ≤ 5 years, 1 person (50%) has good comprehension with working time ≤ 5 years, 1 person (50% ) has good understanding comprehension with working time > 10 years, 4 people (50%) have sufficient comprehension with working time > 10 years, 2 persons (25%) have sufficient comprehension with working time ≤ 5 years, 2 persons (25 %) have sufficient comprehension with working time 6-10 years, and 1 person (14.3%) has less comprehension with working time 6-10 years. Analysis using Spearman Rho test obtained p = 0,033 (p˂0,05) with correlation value equal to 0,520. Conclusion: It can be concluded that there is  a moderate relationship between the working time of the radiographers with the procedures comprehension of intra oral periapical radiographic imaging technique at Banjarmasin Hospital.